Extension of frozen-density embedding theory for non-variational embedded wavefunctions - Zech, Alexander; Dreuw, Andreas; Wesolowski, Tomasz A. (The journal of chemical physics, 2019)
In the original formulation, frozen-density embedding theory [T. A. Wesolowski and A. Warshel, J. Phys. Chem. 97, 8050-8053 (1993); T. A. Wesołowski, Phys. Rev. A 77, 012504 (2008)] concerns multi-level simulation methods in which variational methods are used to obtain the embedded NA-electron wavefunction. In this work, an implicit density functional for the total energy is constructed and used to derive a general expression for the total energy in methods in which the embedded NA electrons are treated non-variationally. The formula is exact within linear expansion in density perturbations. Illustrative numerical examples are provided.